A High Fat Diet During Pregnancy and Lactation Induces Cardiac and Renal Abnormalities in GLUT4 +/- Male Mice - Michael Kruse; Ariana Fiallo; Jianling Tao; Katalin Susztak; Kerstin Amann; Ellen B. Katz; Maureen J. Charron (Karger Publishers, 2017)
Background/Aims: Altered nutrients during the in utero (IU) and/or lactation (L) period predispose offspring to cardio-renal diseases in adulthood. This study investigates the effect of a high fat diet (HFD) fed to female mice during IU/L on gene expression patterns associated with heart and kidney failure and hypertension in male offspring. Methods: Female wild type (WT) mice were fed either a HFD or control chow (C) prior to mating with males with a genetic heterozygous deletion of GLUT4 (G4+/-, a model of peripheral insulin resistance and hypertension) and throughout IU/L. After weaning male offspring were placed on a standard rodent chow until 24 weeks of age. Results: All offspring exposed to a maternal HFD showed increased heart and kidney weight and reduced cardiac insulin responsiveness. G4+/- offspring on a HFD displayed early hypertension associated with increased renal gene expression of renin and the AT1- receptors compared to G4+/- on a C diet. This group showed decreased cardiac expression of key genes involved in fatty acid oxidation compared to WT on a C diet. Conclusions: These results indicate an interaction between a HFD diet and genotype during early life development that can enhance susceptibility to cardio-renal diseases later in life.